2017
DOI: 10.3324/haematol.2017.178608
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia modulates the purine salvage pathway and decreases red blood cell and supernatant levels of hypoxanthine during refrigerated storage

Abstract: Hypoxanthine catabolism in vivo is potentially dangerous as it fuels production of urate and, most importantly, hydrogen peroxide. However, it is unclear whether accumulation of intracellular and supernatant hypoxanthine in stored red blood cell units is clinically relevant for transfused recipients. Leukoreduced red blood cells from glucose-6-phosphate dehydrogenase-normal or -deficient human volunteers were stored in AS-3 under normoxic, hyperoxic, or hypoxic conditions (with oxygen saturation ranging from <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
185
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 123 publications
(209 citation statements)
references
References 74 publications
24
185
0
Order By: Relevance
“…Samples stored in AS-1 were characterized by lower levels of citrate (absolute and relative quant graphs are shown in Figures 4.B and 7, respectively), oxaloacetate, homoaconitate and acyl-carnitine C6-DC (Figure 7). The same samples were instead characterized by higher levels of malate and fumarate – byproducts of reactions preserving NADH homeostasis and purine salvage in the presence of aspartate (an almost completely inactive pathway in RBCs 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Samples stored in AS-1 were characterized by lower levels of citrate (absolute and relative quant graphs are shown in Figures 4.B and 7, respectively), oxaloacetate, homoaconitate and acyl-carnitine C6-DC (Figure 7). The same samples were instead characterized by higher levels of malate and fumarate – byproducts of reactions preserving NADH homeostasis and purine salvage in the presence of aspartate (an almost completely inactive pathway in RBCs 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the observed metabolic benefits do not extend to the prevention of storage‐induced fatty acid release and lipid oxidation. The correlation of metabolites from these pathways with surrogate ex vivo indexes of functional outcomes (e.g., cell morphology and osmotic fragility) are relevant in that they confirm and extend the recent observation on the (correlative) role of purine deamination in RBC recovery after transfusion . However, additional functional in vivo measurements (e.g., posttransfusion recovery) will be instrumental to further expand our understanding of the impact of these storage additives on transfusion efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…This observation could also be alternatively explained by increased fluxes through the oxidative PPP, resulting in higher nonoxidative/oxidative PPP intermediate ratios (consistent with higher glucose‐6‐phosphate dehydrogenase activity and thus increased antioxidant capacity in alkaline RBCs). Indeed, we recently appreciated the role that oxidative stress plays in activating AMP deaminase 3 to promote purine deamination and thus hypoxanthine accumulation, a phenomenon that negatively correlates with posttransfusion recovery and is prevented by hypoxic storage (which also induces intracellular alkalinization) . However, direct comparison of hypoxanthine levels in alkaline versus nonalkaline additives (SOLX vs. AS‐3) in unpaired studies showed increases in the former group, also accompanied by higher total levels of nondeaminated purines and ATP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations to energy and redox metabolism may indeed limit RBC capacity to circulate upon transfusion, as historically noted for the storage‐induced depletion of high‐energy phosphate compounds such as adenosine triphosphate (ATP) and, more recently, for the ATP‐breakdown product hypoxanthine . Indeed, the metabolic storage lesion may negatively impact the capacity of transfused RBCs to cope with physiologic challenges such as body temperature, inflammation, and systemic stress present in hypoxic recipients (e.g., patients with sickle cell or critically ill patients).…”
mentioning
confidence: 99%